1989
DOI: 10.1159/000153861
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Conditional Heterozygosity Risks for Young Females in Duchenne Muscular Dystrophy

Abstract: Using the data from daughters of known carriers and from age-paired controls, we present a method for estimating the mean and variance of creatine kinase (CK) and pyruvate kinase (PK) in pre-menarchal and early adolescent Duchenne muscular dystrophy (DMD) carriers. CK and PK means and variances were estimated for different age ranges; it is shown that among DMD carriers the levels of both enzymes decrease linearly with age. A discriminant analysis was further performed for the estimation of biochemical risks f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Measurement of CK levels is still considered to be a very important part of carrier detection and the use of age related normal values improves its usefulness. 8 In very general terms, histopathological assessment of muscle biopsies can potentially differentiate myopathic from neurogenic disorders and dystrophic from inflammatory processes. Furthermore, although the assessment may be regarded as a rather subjective process, in the case of DMD the pattern of histological abnormalities is sufficiently characteristic to pose few problems for the experienced observer.…”
Section: Ck Levels and Histopathologymentioning
confidence: 99%
“…Measurement of CK levels is still considered to be a very important part of carrier detection and the use of age related normal values improves its usefulness. 8 In very general terms, histopathological assessment of muscle biopsies can potentially differentiate myopathic from neurogenic disorders and dystrophic from inflammatory processes. Furthermore, although the assessment may be regarded as a rather subjective process, in the case of DMD the pattern of histological abnormalities is sufficiently characteristic to pose few problems for the experienced observer.…”
Section: Ck Levels and Histopathologymentioning
confidence: 99%
“…The observation that serum CK decreases with age in young carriers [Thompson et al, 1967;Moser and Vogt, 1974;Lange and Zatz, 1979;Passos-Bueno et al, 1989; the present study] has suggested that this might occur due to the progressive elimination of dystrophic fibers which contribute to the release of serum enzymes to the blood. However, before DNA analysis it was not possible to determine if a female was an obligate carrier of the DMD gene before the birth of an affected child.…”
Section: Serum Ck In Dmd Carriersmentioning
confidence: 50%
“…In affected male DMD/Becker muscular dystrophy (BMD) patients, it was shown that the activity of CK in serum gradually decreases with advancing age due to the progressive elimination of dystrophic fibers [Pennington, 1980;Rowland, 1980;Edwards et al, 1983;Hoffman et al, 1987Hoffman et al, , 1988Zatz et al, 1991]. It was suggested by us and others, that the serum CK activity in female heterozygotes seems to decrease also with age due to the same mechanism observed in affected boys [Dreyfus et al, 1966;Thompson et al, 1967;Lange and Zatz, 1979;Zatz et al, , 1998Passos-Bueno et al, 1989]. However, in the premolecular era it was not possible to identify among young ''at-risk'' females those who were obligate carriers of the DMD mutated gene.…”
Section: Introductionmentioning
confidence: 91%
“…It was concluded that CK and PK levels were under genetic control in normal twins. Several studies reported that some factors, such as physical exercise [9], age [11], race [12,21], pregnancy [22], and seasonal variation [13], may influence CK and PK activities in healthy subjects. However, little is known about the influence of genetic and environmental factors on ICDH activity.…”
Section: Introductionmentioning
confidence: 99%